A Systematic Review and Meta-Analysis of the Sustainable Impact of Sewage Sludge Application on Soil Organic Matter and Nutrient Content - Paganini, Enzo Antonio Lecciolle; Silva, Rafael Barroca [UNESP]; Ribeiro Roder, Ludmila; Guerrini, Iraê Amaral [UNESP]; Capra, Gian Franco; Grilli, Eleonora; Ganga, Antonio (MDPI, 2024)
The increasing scarcity of natural resources makes the linear production model unsustainable, highlighting the need for more sustainable practices under the umbrella of circular economic principles. Sewage sludge emerges as a promising solution to provide soil organic matter (SOM) and nutrients. This meta-analysis evaluated the impacts of three levels of sludge application (low, medium, and high) on organic matter (OM), nitrogen (N), phosphorus (P), copper (Cu), and zinc (Zn) contents, considering different areas and experimental conditions worldwide. The analysis included 37 studies and 355 comparisons, after screening 7625 records, following the 2020 PRISMA protocol. The effects of sludge concentrations, continents, and types of experiment (field or greenhouse) were evaluated. Sewage sludge application significantly increased OM, N, Cu, and Zn levels, mainly at medium and high rates. The largest effects were observed in greenhouses, suggesting variation by location and environment. Moderators explained a part of the variation in the results, but the residual heterogeneity test revealed that there is still unexplained variability.
Keywords: byproduct; copper; nitrogen; organic matter; phosphorus; PRISMA protocol; sewage sludge; zinc